Research Techniques Made Simple: Animal Models of Wound Healing - Grada, Ayman; Mervis, Joshua; Falanga, Vincent (Journal of investigative dermatology, 2018)
Animal models have been developed to study the complex cellular and biochemical processes of wound repair and to evaluate the efficacy and safety of potential therapeutic agents. Several factors can influence wound healing. These include aging, infection, medications, nutrition, obesity, diabetes, venous insufficiency, and peripheral arterial disease. Lack of optimal preclinical models that are capable of properly recapitulating human wounds remains a significant translational challenge. Animal models should strive for reproducibility, quantitative interpretation, clinical relevance, and successful translation into clinical use. In this concise review, we discuss animal models used in wound experiments including mouse, rat, rabbit, pig, and zebrafish, with a special emphasis on impaired wound healing models.